Mechanism of the eukaryotic chaperonin: protein folding in the chamber of secrets - Spiess, Christoph (2004)
Chaperonins are key components of the cellular chaperone machinery. These large, cylindrical complexes contain a central cavity that binds to unfolded polypeptides and sequesters them from the cellular environment. Substrate folding then occurs in this central cavity in an ATP-dependent manner. The eukaryotic chaperonin TCP-1 ring complex (TRiC, also called CCT) is indispensable for cell survival because the folding of an essential subset of cytosolic proteins requires TRiC, and this function cannot be substituted by other chaperones. This specificity indicates that TRiC has evolved structural and mechanistic features that distinguish it from other chaperones. Although knowledge of this unique complex is in its infancy, we review recent advances that open the way to understanding the secrets of its folding chamber.